Culture Model for Non-human Primate Choroid Plexus - Delery, Elizabeth C.; MacLean, Andrew G. (Frontiers in Cellular Neuroscience, 2019)
While there are murine and rat choroid plexus epithelial cell cultures, a translationally relevant model for choroid plexus activation and function in primates is still lacking. The rhesus macaque is gold standard for modeling viral infection and activation of CNS, including HIV-associated neurocognitive disorders. We have developed a rhesus macaque choroid plexus epithelial cell culture model which we believe to suitable for studies of inflammation associated with viral infection of the CNS. Epithelial morphology and function were assessed using vimentin, phalloidin, the tight junction protein zonula-occludens-1 (ZO-1), and focal adhesion kinase (FAK). Choroid plexus epithelial cell type was confirmed using immunofluorescence with two proteins highly expressed in the choroid plexus: transthyretin and -klotho. Finally, barrier properties of the model were monitored using pro- and anti-inflammatory mediators (TNF-, the TLR2 agonist PamCys3K, and dexamethasone). We have presented a model of the blood-CSF barrier that will allow study into pro- and anti-inflammatory conditions in the brain, while simultaneously measuring real time changes to epithelial cells.